Connecting and Strengthening Young Aboriginal Men: A Family Wellbeing Pilot Study. Issue 2 (2nd April 2016) - Whiteside, Mary; Klieve, Helen; Millgate, Nigel; Webb, Brad; Gabriel, Zona; McPherson, Lynne; Tsey, Komla
ABSTRACT: A significant proportion of young people in Australia are currently not being engaged in school and other social systems. This article presents the results of a mixed-methods study of a pilot Family Wellbeing intervention designed to enhance the social and emotional wellbeing (SEWB) of young Aboriginal men and improve engagement in education, employment, and other social participation. A questionnaire incorporating the Kessler Psychological Distress Scale and respondent self-assessment SEWB questions was administered to program participants pre and post intervention ( N   =  30) and qualitative data were collected from program organisers ( N   =  6). The results suggest that the Family Wellbeing intervention has the capacity to make a marked contribution to the SEWB of young Aboriginal men; participants experienced strong improvement in capacity to manage relationships, engagement in education and employment, and mental and physical health. The factors that enabled the program to be adapted to the target group and setting are documented.